Fibrosis-4 index is associated with the risk of hepatocellular carcinoma in patients with cirrhosis and nonalcoholic steatohepatitis - Albhaisi, Somaya; Sun, Jing; Sanyal, Arun J. (Frontiers in Oncology, 2023)
Background & Aims: Identification of high-risk patients for hepatocellular carcinoma (HCC) is essential for long term monitoring of nonalcoholic steatohepatitis (NASH) cirrhosis progression. We sought to evaluate the association between Fibrosis-4 (FIB-4) index and incidence of HCC risk among patients with NASH cirrhosis. Methods: We conducted a retrospective cohort study of adult patients with NASH cirrhosis (n= 1,338) who were evaluated in a single medical center between 2005 and 2015. Those who developed HCC were identified through electronic medical records using International Classification of Diseases (ICD) 9 and 10 codes until the end of September 2021. Results: During a median follow-up time of 3.7 years, 157 (11.7%) patients with NASH cirrhosis developed HCC. At index visit, the study population had a median age 57 years, 43% males, 78.8% White, and mean FIB-4 index 4.2. The final multivariable Cox regression model revealed that male sex, BMI 25-29.9 kg/m2, and hypertension were independent factors associated with development of HCC in patients with NASH cirrhosis. Compared to patients with FIB-4 < 1.45, patients with FIB-4 between 1.45-3.25 had a similar hazard of HCC (Hazard Ratio [HR] 1.12, 95% CI: 0.67-1.86, p=0.670), whereas patients with FIB-4 >3.25 had a 1.93 (95% CI: 1.22-3.05, p=0.005) increased hazard of HCC. Conclusions: FIB-4 > 3.25 was an independent factor associated with increased HCC risk among NASH cirrhosis patients. FIB-4 index is a promising tool for determining high-risk patients and may be used in routine clinical practice to monitor risk of HCC in patients with NASH cirrhosis.